The conceptual basis of the formation of linguistic identities of future interpreters - Горошкін, Ігор (Pedagogy of Higher and Secondary Education, 2013)
Goroshkin I. A. The conceptual basis of the formation of linguistic identities of future interpreters. The article presents a generalized point of view on the training of future interpeters at the professional level of methodological concept (approach, principles of teaching), substantial (requirements for the content of training, socio-cultural training), technology (the basic forms, methods and meanings of training, the organization of independent work of students).